2014
DOI: 10.1016/j.jebo.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

When parity promotes peace: Resolving conflict between asymmetric agents

Abstract: Due to the high costs of conflict both in theory and practice, we examine and experimentally test the conditions under which conflict between asymmetric agents can be resolved. We model conflict as a two-agent rent-seeking contest for an indivisible prize. Before conflict arises, both agents may agree to allocate the prize by fair coin flip to avoid the costs of conflict. The model predicts that "parity promotes peace": in the pure-strategy equilibrium, agents with relatively symmetric conflict capabilities ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 48 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…The experimental evidence by and large confirms the discouragement effect (e.g. Fonseca, 2009, Anderson and Freeborn, 2010, Kimbrough et al, 2014. March and Sahm (2017) discusses the contribution to this literature in greater detail.…”
Section: Experimental Contributionssupporting
confidence: 58%
“…The experimental evidence by and large confirms the discouragement effect (e.g. Fonseca, 2009, Anderson and Freeborn, 2010, Kimbrough et al, 2014. March and Sahm (2017) discusses the contribution to this literature in greater detail.…”
Section: Experimental Contributionssupporting
confidence: 58%
“…2 Both of these policies aim to reduce 1 Experimental studies found support for the discouragement effect in all-pay auctions (Davis and Reilly, 1998;Deck and Sheremeta, 2012;Fehr and Schmidt, 2015), lottery contests (Fonseca, 2009;Kimbrough et al, 2014), rank-order tournaments (Weigelt et al, 1989;Schotter and Weigelt, 1992), and real-effort tournaments (Cason et al, 2010;Gill and Prowse, 2012). 2 Kaplan and Wettstein (2006) argue that if caps are not rigid, the existence of a cap will not result in increased spending.…”
Section: Introductionmentioning
confidence: 99%
“…When there is perfect information and the costs of conflict are relatively high, settlements are likely to occur according to certain asymmetries between the contestants [30,31]. However, when there is uncertainty and differences are hard to detect, conflicts are more likely to ensue as the contestants uncover who is stronger (or more aggressive) and who is weaker [32,33].…”
Section: The Evolutionary Biology Perspective On Conflictmentioning
confidence: 99%